A hydrogen fuel cell positive electrode material, a preparation method and applications thereof

CN122992097APending Publication Date: 2026-10-27SHANDONG HAIHUA CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611477478.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

由该专利的附图可见其产品尺寸不均且大部分Co3O4纳米球表面无明显孔道结构,不利于电解液进入及反应产物脱出,易堵塞活性位点;并且当钌元素含量提升时,其中空结构明显受到破坏,且大量的颗粒聚集在Co3O4纳米球表面形成团聚,造成活性位点数量减少、原子利用率低的问题,直接降低其反应催化活性

Benefits of technology

(1)本发明的氢燃料电池正极材料的制备方法,能够通过流程简洁、重复性好、适合工业化生产的制备工艺,制得结构规整、尺寸均匀、催化活性高、长期循环稳定性好的中空纳米球状钌掺杂Co3O4氧还原催化正极材料;具体的:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992097A_ABST
    Figure CN122992097A_ABST
Patent Text Reader

Abstract

The application provides a hydrogen fuel cell positive electrode material, a preparation method and application thereof, and relates to the field of hydrogen fuel cell electrode materials.The preparation method comprises the following steps: dissolving a cobalt salt, a ruthenium salt and resorcinol in deionized water, adding sodium citrate, and adjusting the pH to 7.2-7.8 to obtain a precursor solution; adding formaldehyde at a temperature of 60-80 DEG C, stirring until turbid, and constant-temperature standing and reaction to obtain a solid compound; soaking the solid compound in a reducing agent solution, washing, drying, and calcining to obtain hollow nanometer spherical ruthenium-doped Co3O4.The application can prepare a hydrogen fuel cell positive electrode material with a regular structure, uniform particle size, high catalytic activity and good long-term cycle stability through a preparation process which is simple in flow, good in repeatability and suitable for industrial production; the half-wave potential of the hydrogen fuel cell positive electrode material in an oxygen reduction reaction of a hydrogen fuel cell is 0.82 V, and the continuous stable operation time is more than 140 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hydrogen fuel cell electrode materials, and in particular to a hydrogen fuel cell cathode material, its preparation method, and its application. Background Technology

[0002] Hydrogen fuel cells can directly and efficiently convert hydrogen into electrical energy, offering significant advantages in power density, efficiency, low-temperature start-up, and dynamic response capabilities. They are a key technology for achieving cleaner and more efficient energy. The oxygen reduction reaction (ORR) at the cathode of a hydrogen fuel cell is its core reaction; however, existing hydrogen fuel cell cathode materials suffer from high manufacturing costs, poor stability, and complex preparation processes, severely hindering their industrialization and widespread application.

[0003] Co3O4 has been extensively studied as a matrix material for oxygen reduction catalysis in existing patents and literature. Publicly available patents and existing technologies generally show that constructing hollow nanostructures and doping with metal atoms are the main means to regulate the number of active sites and intrinsic catalytic activity of Co3O4. However, the currently disclosed Co3O4 preparation technology still suffers from problems such as complex preparation process, uneven Co3O4 size, and low atomic utilization, which directly lead to inherent defects such as poor oxygen reduction reaction activity and insufficient long-term operational stability when Co3O4 is used as the positive electrode of hydrogen fuel cells.

[0004] Chinese patent document CN121775867A discloses a hollow spherical ruthenium-doped cobalt tetroxide catalyst material, its preparation method, and its application. This patent involves mixing ruthenium salt, cobalt salt, alkali, and solvent, reacting the mixture, and then calcining it to obtain the hollow spherical ruthenium-doped Co3O4 catalyst. It forms spherical aggregates through a solvothermal reaction, relying on ion nucleation and growth. As shown in the attached figures of this patent, the product has uneven size, and most of the Co3O4 nanospheres lack obvious pore structures on their surface, which is not conducive to electrolyte entry and reaction product extraction, easily clogging active sites. Furthermore, when the ruthenium content increases, its hollow structure is significantly damaged, and a large number of particles aggregate on the surface of the Co3O4 nanospheres, forming agglomerates, resulting in a reduction in the number of active sites and low atomic utilization, directly reducing its catalytic activity.

[0005] Based on this, a method for preparing a hydrogen fuel cell cathode material is provided. This method can produce hollow nanospheres of ruthenium-doped Co3O4 oxygen reduction catalytic cathode material with regular structure, uniform size, high catalytic activity, and good long-term cycle stability through a simple, reproducible, and industrially suitable preparation process. This method has significant technical significance and research value. Summary of the Invention

[0006] To address the technical problems existing in the prior art, this invention provides a method for preparing a hydrogen fuel cell cathode material. This method enables the preparation of hollow nanospheres of ruthenium-doped Co3O4 oxygen reduction catalytic cathode material with regular structure, uniform size, high catalytic activity, and good long-term cycle stability through a simple, reproducible, and industrially suitable preparation process.

[0007] The present invention also provides a hydrogen fuel cell cathode material prepared by the aforementioned method.

[0008] The present invention also provides applications of the aforementioned hydrogen fuel cell cathode material.

[0009] To solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a positive electrode material for a hydrogen fuel cell includes the following steps: Step S01: Dissolve cobalt salt, ruthenium salt, and resorcinol in deionized water, mix thoroughly, add sodium citrate, adjust the pH to 7.2-7.8, react at room temperature to obtain the precursor solution; Step S02: Heat the precursor solution to 60-80℃, keep it at the temperature and add formaldehyde, stir continuously until the solution becomes turbid, stop stirring, let it stand at a constant temperature of 60-80℃ for reaction, and collect the solid. Soak the solid in a reducing agent solution, take it out after soaking at room temperature, wash, dry and calcine to obtain hollow nanosphere ruthenium-doped Co3O4, which is the cathode material of hydrogen fuel cells.

[0010] Preferably, the cobalt salt is one of the following: cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, or cobalt acetate; Ruthenium salts are one of the following: ruthenium trichloride, ruthenium acetate, and ruthenium acetylacetonate.

[0011] Preferably, in step S01, the molar ratio of cobalt to ruthenium is 1:0.01-0.1; The ratio of the added resorcinol weight to the total weight of cobalt and ruthenium salts is 1:0.1-0.2.

[0012] Preferably, in step S01, the mass ratio of resorcinol to deionized water is 1:5-8; The weight of sodium citrate added is 1-2% of the weight of resorcinol.

[0013] Preferably, in step S01, the reaction time at room temperature is 1-3 hours.

[0014] Preferably, in step S02, the molar ratio of formaldehyde to resorcinol contained in the precursor solution is 2-3:1.

[0015] Preferably, in step S02, the reducing agent solution is one of the following: sodium sulfite solution, sodium bisulfite solution, ascorbic acid solution, or hydrazine hydrate solution; The mass-to-volume ratio of the solid to the reducing agent solution is 1g:10-20mL.

[0016] Preferably, in step S02, the constant temperature static reaction time is 1-5 hours; the room temperature soaking time is 30-60 minutes. The calcination temperature is 600-800℃, and the calcination time is 2-8 hours.

[0017] A positive electrode material for hydrogen fuel cells is prepared using the aforementioned preparation method.

[0018] Application of the aforementioned hydrogen fuel cell cathode material in the preparation of hydrogen fuel cell cathodes.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The method for preparing the hydrogen fuel cell cathode material of the present invention can produce hollow nanosphere ruthenium-doped Co3O4 oxygen reduction catalytic cathode material with regular structure, uniform size, high catalytic activity, and good long-term cycle stability through a simple, reproducible, and industrially suitable preparation process; specifically: In step S01, after dissolving cobalt salt, ruthenium salt, and resorcinol in deionized water, sodium citrate is added to effectively prevent the addition of metal ions Co. 2+ Ru 3+ They aggregate with each other; simultaneously, adjusting the pH of the system to 7.2-7.8 can enhance the complexation of sodium citrate with Co. 2+ Ru 3+ The ability of sodium citrate to complex metal ions creates a steric hindrance effect, preventing Co from... 2+ Ru 3+ It is encapsulated in resorcinol-formaldehyde resin balls; and the pH value is controlled at 7.2-7.8, which can also prevent the metal precipitation caused by excessive alkalinity of the solution.

[0020] In step S02, in an alkaline environment, formaldehyde and resorcinol undergo a condensation reaction to generate resorcinol-formaldehyde resin balls at 80°C; metal ions Co 2+ Ru 3+ The complex species with sodium citrate contains abundant carboxyl and hydroxyl groups. Due to steric hindrance, this complex is uniformly adsorbed and coated on the surface of resorcinol-formaldehyde resin spheres. Then, a reducing agent solution is used to treat the dark red solid compound, causing the Co groups adsorbed and coated on the surface of the resorcinol-formaldehyde resin to... 2+ Ru 3+Pre-reduction precipitation of metal sites ensures uniform crystallization during subsequent calcination, thereby improving the stability and porosity of the hollow nanosphere structure. Furthermore, the internal structure of the resin template is not damaged before calcination, resulting in significantly improved particle size uniformity. Calcination is then performed in an air atmosphere, where the resorcinol-formaldehyde resin spheres decompose into carbon dioxide and water, forming a hollow structure. Simultaneously, the pre-reduced metal sites on the surface are oxidized in situ in air, completing the uniform doping of ruthenium into the Co3O4 lattice, thus producing hollow ruthenium-doped Co3O4 nanospheres.

[0021] (2) The preparation method of the hydrogen fuel cell cathode material of the present invention, by adding sodium citrate in step S01 and adjusting the pH value to 7.2-7.8, and by using a reducing agent solution for reduction treatment in step S02, forms a simple and mild preparation process system; compared with the existing traditional preparation processes such as co-precipitation, hard template, and hydrothermal, the present invention uses sodium citrate to complex Co 2+ Ru 3+ By combining pH adjustment and synergistic reducing agent treatment, the metal ion Co 2+ Ru 3+ Uniform nucleation and growth on the surface of resorcinol-formaldehyde resin spheres simplifies the operation steps, shortens the reaction time, eliminates the need for complex treatments, and achieves precise control of the preparation process. Furthermore, by employing a reducing agent solution for immersion treatment, combined with the aforementioned sodium citrate complexation, the metal ion complexes adsorbed and encapsulated on the surface of the resorcinol-formaldehyde resin spheres due to steric hindrance are reduced and precipitated in advance to form metal sites. This ensures uniform crystallization during subsequent calcination, thereby improving the stability and porosity of the hollow nanosphere structure. Moreover, the internal structure of the resin template is not damaged before calcination, resulting in significantly improved particle size uniformity.

[0022] (3) The hydrogen fuel cell cathode material of the present invention (i.e., hollow nanosphere-shaped ruthenium-doped Co3O4) has a hollow structure and abundant pore characteristics, which can effectively accelerate the diffusion rate of reaction substrates and products, reduce mass transfer resistance, reduce the energy consumption of catalytic reaction, and at the same time avoid the accumulation of reaction products on the catalyst surface, further improving catalytic efficiency and stability. Meanwhile, its hollow nanosphere structure has good structural stability, is not prone to collapse or agglomeration, reduces the loss of active sites of the catalyst during the reaction process, and significantly improves the cycle stability and service life of the catalyst; effectively solves the pain points of easy deactivation and short service life of existing catalytic materials, improves the economy and reliability of practical applications, and has good application prospects. Attached Figure Description

[0023] Figure 1 The image shows a scanning electron microscope (SEM) image of the hollow ruthenium-doped Co3O4 nanospheres prepared in Example 1.

[0024] Figure 2 The image shows a scanning electron microscope (SEM) image of the hollow ruthenium-doped Co3O4 nanospheres prepared in Example 2.

[0025] Figure 3 The image shows a scanning electron microscope (SEM) image of the hydrogen fuel cell cathode material prepared in Comparative Example 1.

[0026] Figure 4 The image shows a scanning electron microscope (SEM) image of the hydrogen fuel cell cathode material prepared in Comparative Example 2.

[0027] Figure 5 The image shows the XRD pattern of the hollow ruthenium-doped Co3O4 nanospheres prepared in Example 1.

[0028] Figure 6 ORR potential diagrams of hollow ruthenium nanospheres doped with Co3O4 and commercial Pt / C electrodes prepared in Example 1.

[0029] Figure 7 The ORR potential diagram is for the hydrogen fuel cell cathode material prepared in Comparative Example 3.

[0030] Figure 8 ORR stability test results for hollow ruthenium nanospheres doped with Co3O4 prepared in Example 1. Detailed Implementation

[0031] To provide a clearer understanding of the technical features, objectives, and effects of this invention, specific embodiments are now described. It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0032] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments of the present invention. As used herein, "first," "second," etc., are used to distinguish similar objects and are not used to describe a particular order or sequence. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0033] In a first aspect, embodiments of the present invention provide a method for preparing a positive electrode material for a hydrogen fuel cell, comprising the following steps: Step S01: Dissolve cobalt salt, ruthenium salt, and resorcinol in deionized water, mix thoroughly, add sodium citrate, adjust the pH to 7.2-7.8 with an alkaline solution, stir the reaction at room temperature to obtain a homogeneous and stable precursor solution; Step S02: Heat the precursor solution to 60-80℃, keep it at the temperature and add formaldehyde solution, stir continuously until the solution becomes turbid, stop stirring, let it stand at a constant temperature of 60-80℃ for reaction, collect the solid matter to obtain a dark red solid compound; immerse the dark red solid compound in a reducing agent solution, take it out after immersion at room temperature, wash, dry and calcine to obtain hollow nanosphere ruthenium-doped Co3O4, which is the positive electrode material of hydrogen fuel cells.

[0034] In step S01 of this embodiment of the invention, after dissolving cobalt salt, ruthenium salt, and resorcinol in deionized water, sodium citrate is added to effectively prevent the addition of metal ions Co. 2+ Ru 3+ They aggregate with each other; simultaneously, adjusting the pH of the system to 7.2-7.8 can enhance the complexation of sodium citrate with Co. 2+ Ru 3+ The ability of sodium citrate to complex metal ions creates a steric hindrance effect, preventing Co from... 2+ Ru 3+ It is encapsulated in resorcinol-formaldehyde resin balls; and the pH value is adjusted to 7.2-7.8 to avoid the formation of metal precipitates due to excessive alkalinity of the solution.

[0035] In step S02, in an alkaline environment, formaldehyde and resorcinol undergo a condensation reaction to generate resorcinol-formaldehyde resin balls at 80°C; metal ions Co 2+ Ru 3+ The complex species with sodium citrate contains abundant carboxyl and hydroxyl groups. Due to steric hindrance, this complex is uniformly adsorbed and coated on the surface of resorcinol-formaldehyde resin spheres. Then, a reducing agent solution is used to treat the dark red solid compound, causing the Co groups adsorbed and coated on the surface of the resorcinol-formaldehyde resin to... 2+ Ru 3+ Pre-reduction precipitation of metal sites ensures uniform crystallization during subsequent calcination, thereby improving the stability and porosity of the hollow nanosphere structure. Furthermore, the internal structure of the resin template is not damaged before calcination, resulting in significantly improved particle size uniformity. Calcination is then performed in an air atmosphere, where the resorcinol-formaldehyde resin spheres decompose into carbon dioxide and water, forming a hollow structure. Simultaneously, the pre-reduced metal sites on the surface are oxidized in situ in air, completing the uniform doping of ruthenium into the Co3O4 lattice, thus producing hollow ruthenium-doped Co3O4 nanospheres.

[0036] Preferably, in step S01, the molar ratio of cobalt to ruthenium is controlled to be 1:0.01-0.1 (i.e., the molar ratio of cobalt salt to ruthenium salt is 1:0.01-0.1).

[0037] Preferably, in step S01, the cobalt salt is one of the following: cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, or cobalt acetate; and the ruthenium salt is one of the following: ruthenium trichloride, ruthenium acetate, or ruthenium acetylacetonate.

[0038] Preferably, in step S01, the ratio of the added weight of resorcinol to the total weight of cobalt salt and ruthenium salt is 1:0.1-0.2.

[0039] Preferably, in step S01, the mass ratio of resorcinol to deionized water is 1:5-8.

[0040] Preferably, in step S01, the weight of sodium citrate added is 1-2% of the weight of resorcinol.

[0041] Preferably, in step S01, the alkaline solution is ammonia or sodium hydroxide aqueous solution; the concentration of ammonia is 0.1-1 mol / L; and the concentration of sodium hydroxide aqueous solution is 0.1-0.5 mol / L.

[0042] Preferably, in step S01, the stirring reaction at room temperature takes 1-3 hours.

[0043] Preferably, in step S02, the concentration of the formaldehyde solution is 35-45 wt%; the molar ratio of formaldehyde in the formaldehyde solution to resorcinol in the precursor solution is 2-3:1.

[0044] Preferably, in step S02, the reducing agent solution is one of the following: sodium sulfite solution, sodium bisulfite solution, ascorbic acid solution, or hydrazine hydrate solution; the concentration of the sodium sulfite solution is 0.05-0.1 mol / L; the concentration of the sodium bisulfite solution is 0.05-0.1 mol / L; the concentration of the ascorbic acid solution is 0.08-0.12 mol / L; and the concentration of the hydrazine hydrate solution is 0.01-0.05 mol / L.

[0045] Preferably, in step S02, the mass-to-volume ratio of the dark red solid compound to the reducing agent solution is 1g:10-20mL.

[0046] Preferably, in step S02, the constant temperature static reaction time is 1-5 hours; the room temperature soaking time is 30-60 minutes.

[0047] Preferably, in step S02, calcination is carried out in an air atmosphere, the calcination temperature is 600-800℃, and the calcination time is 2-8h.

[0048] Secondly, embodiments of the present invention also provide a hydrogen fuel cell cathode material prepared using the aforementioned method.

[0049] Thirdly, embodiments of the present invention also provide the application of the aforementioned hydrogen fuel cell cathode material.

[0050] In this embodiment of the invention, the hydrogen fuel cell cathode material (i.e., hollow nanosphere-shaped ruthenium-doped Co3O4) prepared by the aforementioned method can effectively accelerate the diffusion rate of the reaction substrate and products, reduce mass transfer resistance, and lower the energy consumption of the catalytic reaction. Simultaneously, it avoids the accumulation of reaction products on the catalyst surface, further improving catalytic efficiency and stability. Furthermore, its hollow nanosphere structure possesses good structural stability, is not prone to collapse or aggregation, effectively reducing the loss of active sites during the reaction process, and significantly improving the catalyst's cycle stability and lifespan.

[0051] To enable those skilled in the art to more clearly understand the technical solution of the present invention, the present invention will be further described below with reference to some specific embodiments. Unless otherwise specified, the experimental methods used in each embodiment are conventional methods; unless otherwise specified, the reagents and materials used in each embodiment are commercially available products.

[0052] Example 1 This embodiment provides a method for preparing a positive electrode material for a hydrogen fuel cell, specifically including the following steps: (1) 1.19 g cobalt chloride hexahydrate, 0.104 g ruthenium trichloride and 12.94 g resorcinol were dissolved in 70 mL of deionized water at a molar ratio of cobalt to ruthenium of 1:0.1 and a total mass ratio of resorcinol to cobalt and ruthenium metal salt of 1:0.1. The mixture was stirred continuously, and 0.259 g of sodium citrate (2% of the mass of resorcinol) was added. The pH of the system was adjusted to 7.2 by adding 0.1 mol / L sodium hydroxide aqueous solution. The mixture was stirred at room temperature for 3 h to obtain a homogeneous and stable precursor solution. (2) After heating the precursor solution to 80°C and keeping it at that temperature, add 16.4 mL of formaldehyde solution with a concentration of 40 wt% and a molar ratio of formaldehyde to resorcinol of 2:1. Continue stirring until the solution becomes turbid. Let it stand at a constant temperature for 3 hours and collect the solid to obtain 15.3 g of dark red solid compound. Soak the dark red solid compound in 230 mL of sodium sulfite solution (concentration of 0.1 mol / L) at room temperature for 30 minutes. After soaking, take it out, wash and dry it, and calcine it at 600°C for 4 hours in an air atmosphere to obtain hollow nanosphere ruthenium-doped Co3O4, which is the hydrogen fuel cell cathode material of Example 1.

[0053] This embodiment also provides a hydrogen fuel cell cathode material prepared using the aforementioned method.

[0054] Example 2 This embodiment provides a method for preparing a positive electrode material for a hydrogen fuel cell, specifically including the following steps: (1) 2.91g of cobalt nitrate hexahydrate, 0.104g of ruthenium trichloride and 15.07g of resorcinol were dissolved in 80mL of deionized water at a molar ratio of cobalt to ruthenium of 1:0.05 and a total mass ratio of resorcinol to cobalt and ruthenium metal salt of 1:0.2. The mixture was stirred continuously, and 0.314g of sodium citrate (2% of the mass of resorcinol) was added. The pH of the system was adjusted to 7.5 by adding 0.1mol / L ammonia solution dropwise. The mixture was stirred at room temperature for 2h to obtain a homogeneous and stable precursor solution. (2) After heating the precursor solution to 70°C and keeping it at that temperature, add 19 mL of formaldehyde solution with a concentration of 40 wt% and a molar ratio of formaldehyde to resorcinol of 2:1. Continue stirring until the solution becomes turbid. Let it stand at a constant temperature for 5 h and collect the solid to obtain 19.7 g of dark red solid compound. Soak the dark red solid compound in 390 mL of ascorbic acid solution (concentration of 0.1 mol / L) at room temperature for 40 min and then take it out. After washing and drying, calcine it at 700°C for 3 h in an air atmosphere to obtain hollow nanosphere ruthenium-doped Co3O4, which is the hydrogen fuel cell cathode material of Example 2.

[0055] This embodiment also provides a hydrogen fuel cell cathode material prepared using the aforementioned method.

[0056] Example 3 This embodiment provides a method for preparing a positive electrode material for a hydrogen fuel cell, specifically including the following steps: (1) 1.19 g of cobalt chloride hexahydrate, 0.02 g of ruthenium acetylacetonate and 8.07 g of resorcinol were dissolved in 60 mL of deionized water at a molar ratio of cobalt to ruthenium of 1:0.01 and a total mass ratio of resorcinol to cobalt and ruthenium metal salt of 1:0.15. The mixture was stirred continuously, and 0.161 g of sodium citrate (2% of the mass of resorcinol) was added. The pH of the system was adjusted to 7.8 by adding 0.1 mol / L sodium hydroxide aqueous solution. The mixture was stirred at room temperature for 1 h to obtain a homogeneous and stable precursor solution. (2) After heating the precursor solution to 60°C and keeping it at that temperature, add 5.1 mL of formaldehyde solution with a concentration of 40 wt% and a molar ratio of formaldehyde to resorcinol of 3:1. Continue stirring until the solution becomes turbid. Let the reaction stand at a constant temperature for 1 h and collect the solid to obtain 10.4 g of dark red solid compound. Soak the dark red solid compound in 200 mL of hydrazine hydrate solution (concentration of 0.01 mol / L) at room temperature for 60 min. After soaking, take it out, wash and dry it, and calcine it at 800°C for 2 h in an air atmosphere to obtain hollow nanosphere ruthenium-doped Co3O4, which is the hydrogen fuel cell cathode material of Example 3.

[0057] This embodiment also provides a hydrogen fuel cell cathode material prepared using the aforementioned method.

[0058] Comparative Example 1 Comparative Example 1 adopts the technical solution of Example 1, except that sodium citrate is not added in step (1) of Comparative Example 1, and the pH is not adjusted; other operations and process parameters are the same as in Example 1. The specific steps are as follows: (1) Dissolve 1.19 g cobalt chloride hexahydrate, 0.104 g ruthenium trichloride and 12.94 g resorcinol in 70 mL of deionized water at a molar ratio of cobalt to ruthenium of 1:0.1 and a total mass ratio of resorcinol to cobalt and ruthenium metal salt of 1:0.1. Stir at room temperature for 3 h to obtain the precursor solution. (2) After heating the precursor solution to 80°C and keeping it at that temperature, add 16.4 mL of 40% formaldehyde solution with a molar ratio of 2:1 between formaldehyde and resorcinol. Stir continuously until the solution becomes turbid. Let it stand at a constant temperature for 3 hours and collect the solid to obtain a dark red solid compound. Soak the dark red solid compound in 230 mL of sodium sulfite solution (0.1 mol / L) at room temperature for 30 minutes. After soaking, wash and dry it, calcine it at 600°C for 4 hours in air to obtain the hydrogen fuel cell cathode material of Comparative Example 1.

[0059] Comparative Example 2 Comparative Example 2 uses the technical solution of Example 1, except that sodium citrate is added after the resorcinol-formaldehyde resin is generated in Comparative Example 2; all other operations and process parameters are the same as in Example 1. The specific steps are as follows: (1) Dissolve 1.19 g cobalt chloride hexahydrate, 0.104 g ruthenium trichloride and 12.94 g resorcinol in 70 mL of deionized water at a molar ratio of cobalt to ruthenium of 1:0.1 and a total mass ratio of resorcinol to cobalt and ruthenium metal salt of 1:0.1. Stir at room temperature for 3 h to obtain the precursor solution. (2) After heating the precursor solution to 80°C and keeping it warm, add 16.4 mL of 40% formaldehyde solution. The molar ratio of formaldehyde to resorcinol is 2:1. Continue stirring until the solution becomes turbid. Add 0.259 g of sodium citrate, which accounts for 2% of the mass of resorcinol in step (1). Add 0.1 mol / L sodium hydroxide aqueous solution to adjust the pH of the system to 7.2. Let the reaction stand at a constant temperature for 3 h. Collect the solid to obtain a dark red solid compound. Soak the dark red solid compound in 230 mL of sodium sulfite solution (concentration of 0.1 mol / L) at room temperature for 30 min. After soaking, wash and dry, calcine at 600°C for 4 h in air atmosphere to obtain the hydrogen fuel cell cathode material of Comparative Example 2.

[0060] Comparative Example 3 Comparative Example 3 adopts the technical solution of Example 1, except that in step (2), Comparative Example 3 does not use a reducing agent solution (sodium sulfite solution) for treatment; other operations and process parameters are the same as in Example 1. The specific steps are as follows: (1) 1.19 g cobalt chloride hexahydrate, 0.104 g ruthenium trichloride and 12.94 g resorcinol were dissolved in 70 mL of deionized water at a molar ratio of cobalt to ruthenium of 1:0.1 and a total mass ratio of resorcinol to cobalt and ruthenium metal salt of 1:0.1. The mixture was stirred continuously, and 0.259 g of sodium citrate (2% of the mass of resorcinol) was added. The pH of the system was adjusted to 7.2 by adding 0.1 mol / L sodium hydroxide aqueous solution. The mixture was stirred at room temperature for 3 h to obtain a homogeneous and stable precursor solution. (2) After heating the mixed solution to 80°C and keeping it at that temperature, add 16.4 mL of a 40 wt% formaldehyde solution with a molar ratio of formaldehyde to resorcinol of 2:1. Continue stirring until the solution becomes turbid, and let it stand at a constant temperature for 3 h. Collect the solid to obtain a dark red solid compound. After washing and drying, the dark red solid compound is calcined at 600°C for 4 h in air to obtain the hydrogen fuel cell cathode material of Comparative Example 3.

[0061] Experimental Example 1 Scanning electron microscopy (SEM) tests were performed on the hydrogen fuel cell cathode materials prepared in Examples 1-2, and the results are as follows: Figure 1-2 As shown in the figure. In Comparative Example 1, sodium citrate was not added and the pH was not adjusted; in Comparative Example 2, sodium citrate was added after the resorcinol-formaldehyde resin was generated; the hydrogen fuel cell cathode materials prepared in Comparative Examples 1 and 2 were subjected to scanning electron microscopy tests, and the results are shown in the figure. Figure 3-4 As shown.

[0062] Depend on Figure 1-2 The scanning electron microscope (SEM) images show that the hydrogen fuel cell cathode materials of Examples 1-2 are assembled from a large number of nanoscale particles, forming a rich porous structure. This is a typical characteristic of hollow nanospheres, providing high specific surface area and efficient mass transfer channels. Simultaneously, the hollow nanospheres are well dispersed, with no aggregation. Figure 3 The scanning electron microscope images show that the metal ion Co in Comparative Example 1... 2+ Ru 3+ Without the complexing protection of sodium citrate, the calcined product exhibits a fragmented and irregular morphology, uneven size, and forms obvious aggregates. Figure 4The scanning electron microscope (SEM) images show that in Comparative Example 2, sodium citrate was added only after the polycondensation reaction was completed (i.e., after the resorcinol-formaldehyde resin spheres were formed). The later-added sodium citrate could not penetrate the resin spheres to achieve effective complexation, leading to damage to the hollow structure integrity during subsequent calcination as the resin carbonized and oxidized. This resulted in material collapse and agglomeration, making it impossible to prepare hollow nanospheres. This verifies that in the preparation of hydrogen fuel cell cathode materials, by adding 1-2% sodium citrate and adjusting the pH to 7.2-7.8 for complexation, the invention can ensure uniform dispersion of metal ions and avoid agglomeration. Simultaneously, treatment with a synergistic reducing agent solution can enhance the adsorption and coating of Co metal ions on the surface of the resorcinol-formaldehyde resin. 2+ Ru 3+ Pre-reduction precipitation to form metal sites ensures uniform crystallization during subsequent calcination, thereby improving the stability and porosity of the hollow nanosphere structure and ensuring uniform nanoparticle size. This confirms the effectiveness of the technology in this invention, which uses sodium citrate complexation, pH adjustment to 7.2-7.8, and the synergistic effect of the reducing agent.

[0063] X-ray diffraction analysis was performed on the hydrogen fuel cell cathode material prepared in Example 1. The specific results are as follows: Figure 5 As shown. Figure 5 The positions of all diffraction peaks perfectly match those of the standard Co3O4 (PDF#43-1003) card, with no extra impurity peaks, proving that the product is pure-phase Co3O4. The absence of other cobalt oxides (such as CoO, Co2O3) or independent ruthenium phases (such as RuO2, metallic Ru) indicates that ruthenium has been successfully doped into the Co3O4 lattice, rather than forming an independent phase. Furthermore, the sharp diffraction peaks and narrow full width at half maximum (FWHM) indicate good crystallinity and uniform grain size; the lack of significant peak broadening demonstrates that the calcination and doping control of this invention not only did not destroy the spinel crystal structure of Co3O4 but also effectively ensured uniform ruthenium doping.

[0064] Experimental Example 2 The hydrogen fuel cell cathode materials prepared in Example 1 and Comparative Example 3 were used in an alkaline environment (0.1 mol / L KOH) to conduct ORR tests on the cathodes of hydrogen-oxygen fuel cells. The specific steps included: 10 μL of electrode material slurry with a concentration of 5 mg / mL (prepared by ultrasonically dispersing 5 mg of hydrogen fuel cell cathode material in a mixed solution containing 0.95 mL isopropanol and 0.05 mL Nafion) was coated onto a rotating disk electrode (electrode area: 0.196 cm²). 2The electrode was used as the working electrode, with a reversible hydrogen electrode and a graphite rod electrode as the reference and counter electrodes, respectively. The experiment was conducted on a CHI760E electrochemical workstation in oxygen-saturated 0.1 mol / L KOH solution at a turntable speed of 1600 rpm, using linear sweep voltammetry (LSV) and stability testing. Specific results are as follows: Figure 6-7 As shown.

[0065] Depend on Figure 6 It is evident that the hollow nanosphere ruthenium-doped Co3O4 material (i.e., the cathode material for hydrogen fuel cells) prepared in Example 1 of this invention has a half-wave potential of 0.82V, exhibiting excellent ORR catalytic performance. This indicates that the abundant pores formed by constructing the hollow structure in this invention can provide a rapid diffusion pathway for oxygen, reaction intermediates, and products: the active centers formed by uniform ruthenium doping optimize the ORR reaction pathway, reduce the reaction energy barrier, accelerate the ORR reaction kinetics, and result in high ORR catalytic activity. Furthermore, compared with the commercial Pt / C electrode in the figure, the half-wave potential of the curve of Example 1 is close to that of the Pt / C curve, indicating that the cathode material of Example 1 has comparable catalytic activity to the commercial Pt / C electrode. Meanwhile, in the diffusion control region of 0.2-0.6V, the current density of Example 1 is significantly greater than that of Pt / C, indicating that the hollow nanosphere structure of the hydrogen fuel cell cathode material of Example 1 provides abundant pores, which is conducive to the rapid diffusion of oxygen, reaction intermediates, and products. Its mass transfer efficiency in an alkaline environment is superior to that of the commercial Pt / C electrode. It can be seen that the hydrogen fuel cell cathode material of Example 1 is superior to the commercial Pt / C electrode in both mass transfer efficiency and current density, and its catalytic activity is comparable to that of the commercial Pt / C electrode.

[0066] Depend on Figure 7 It can be seen that the hydrogen fuel cell cathode material prepared in Comparative Example 3 of this invention has a half-wave potential of only 0.62V in the test. This is because Comparative Example 3 lacks a reduction step, and direct calcination easily leads to the phase separation of cobalt and ruthenium oxides, forming coarse particles and agglomerates; at the same time, metal ions rapidly aggregate and sinter during high-temperature calcination, and the active sites are encapsulated inside the agglomerates, unable to contact the reactants; furthermore, the porous structure is destroyed, increasing the product diffusion resistance and resulting in a significant decrease in the limiting diffusion current density. This demonstrates that this invention, through the synergistic use of a reducing agent, allows the adsorbed and encapsulated metal Co on the surface of resorcinol-formaldehyde resin to be treated, thereby reducing the concentration of the metal Co. 2+ Ru 3+ The early reduction and precipitation of ions to form metal sites can ensure uniform crystallization during subsequent calcination, thereby improving the stability and porosity of the hollow nanosphere structure. The prepared hollow nanosphere ruthenium-doped Co3O4 material has a half-wave potential of 0.82V and exhibits excellent ORR catalytic performance.

[0067] Furthermore, the ORR stability of the hydrogen fuel cell cathode material prepared in Example 1 was tested. Specific results are as follows: Figure 8 As shown. (Through) Figure 8 As can be seen, the hydrogen fuel cell cathode material of Example 1 maintained a current retention rate of over 85% after 140 hours of continuous stable operation in the ORR stability test, demonstrating excellent long-term cycle stability. Analysis revealed that this is because the hollow nanospheres of the cathode material are assembled from nanoscale particles, and the porous shell structure effectively disperses electrochemical stress, preventing structural collapse or breakage during long-term operation, thus maintaining a high specific surface area and active site exposure over the long term. Simultaneously, the doping of ruthenium species into its lattice prevents the dissolution or aggregation of noble metals, maintaining the number and structural stability of ORR active centers over the long term, effectively ensuring its long-term cycle stability.

[0068] Unless otherwise stated, all percentages used in this invention are mass percentages.

[0069] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material for a hydrogen fuel cell, characterized in that, Includes the following steps: Step S01: Dissolve cobalt salt, ruthenium salt, and resorcinol in deionized water, mix thoroughly, add sodium citrate, adjust the pH to 7.2-7.8, react at room temperature to obtain the precursor solution; Step S02: Heat the precursor solution to 60-80℃, keep it at the temperature and add formaldehyde, stir continuously until the solution becomes turbid, stop stirring, let it stand at a constant temperature of 60-80℃ for reaction, and collect the solid. Soak the solid in a reducing agent solution, take it out after soaking at room temperature, wash, dry and calcine to obtain hollow nanosphere ruthenium-doped Co3O4, which is the cathode material of hydrogen fuel cells.

2. The method for preparing the positive electrode material of a hydrogen fuel cell according to claim 1, characterized in that, In step S01, the cobalt salt is one of the following: cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, or cobalt acetate. Ruthenium salts are one of the following: ruthenium trichloride, ruthenium acetate, and ruthenium acetylacetonate.

3. The method for preparing the positive electrode material of a hydrogen fuel cell according to claim 1, characterized in that, In step S01, the molar ratio of cobalt to ruthenium is 1:0.01-0.1; The ratio of the added resorcinol weight to the total weight of cobalt and ruthenium salts is 1:0.1-0.

2.

4. The method for preparing the positive electrode material of a hydrogen fuel cell according to claim 1, characterized in that, In step S01, the mass ratio of resorcinol to deionized water is 1:5-8; The weight of sodium citrate added is 1-2% of the weight of resorcinol.

5. The method for preparing the positive electrode material of a hydrogen fuel cell according to claim 1, characterized in that, In step S01, the reaction time at room temperature is 1-3 hours.

6. The method for preparing the positive electrode material of a hydrogen fuel cell according to claim 1, characterized in that, In step S02, the molar ratio of formaldehyde to resorcinol contained in the precursor solution is 2-3:

1.

7. The method for preparing the positive electrode material of a hydrogen fuel cell according to claim 1, characterized in that, In step S02, the reducing agent solution is one of the following: sodium sulfite solution, sodium bisulfite solution, ascorbic acid solution, or hydrazine hydrate solution; The mass-to-volume ratio of the solid to the reducing agent solution is 1g:10-20mL.

8. The method for preparing the positive electrode material of a hydrogen fuel cell according to claim 1, characterized in that, In step S02, the constant temperature static reaction time is 1-5 hours; the room temperature soaking time is 30-60 minutes. The calcination temperature is 600-800℃, and the calcination time is 2-8 hours.

9. A positive electrode material for a hydrogen fuel cell, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.

10. The application of the hydrogen fuel cell cathode material as described in claim 9 in the preparation of hydrogen fuel cell cathodes.

Citation Information

Patent Citations

  • Hollow spherical ruthenium-doped cobaltosic oxide catalyst material as well as preparation method and application thereof

    CN121775867A